Peluang dan Tantangan Implementasi Sistem Pembayaran Digital bagi Produktivitas UMKM di Era Ekonomi Digital - Herwin Ardianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the opportunities and challenges in implementing digital payment systems to enhance the productivity of Micro, Small, and Medium Enterprises (MSMEs). In the era of growing digital transformation, the adoption of cashless transactions has become a crucial innovation to improve efficiency and competitiveness among MSME players. The findings indicate that the use of digital payment platforms such as QRIS, bank transfers, e-wallets, and card-based e-money offers several advantages, including faster payment processing, reduced risk of calculation errors, and the minimization of counterfeit money usage, which remains an issue in some regions. However, the implementation of digital payments still faces various obstacles on the ground. Certain sectors of MSMEs continue to rely heavily on cash transactions, especially in remote areas where internet connectivity is limited. Furthermore, many business owners still prefer conventional payment methods due to concerns over trust, security, and deeply rooted habits. Demographic factors also influence the level of digital payment adoption. Younger generations tend to be more adaptive to digital technologies, whereas older business owners are generally less familiar and comfortable with using digital devices. These findings suggest that in order to fully leverage the benefits of payment digitalization among MSMEs, strategic efforts are needed. These should include the improvement of digital infrastructure, widespread education and awareness programs, and the development of applications tailored to the specific needs and characteristics of each business sector. Collaboration between the government, financial institutions, and digital service providers is essential in creating an inclusive and user-friendly digital payment ecosystem. By addressing technical barriers and bridging digital literacy gaps, the implementation of digital payments holds significant potential to drive operational efficiency and sustainably boost the productivity of MSMEs.